Changes in Sentence Structure in Students' WhatsApp Communication a Digital Syntax Study - Sosiana Sosiana (Jurnal Multidisiplin Sahombu, 2026)
The rapid expansion of digital communication has significantly transformed students’ written interaction patterns, particularly through messaging platforms such as WhatsApp. This study investigates changes in sentence structure in students’ WhatsApp communication from a digital syntax perspective. Employing a quantitative descriptive analytic approach, the research analyzes 1,850 sentences extracted from 1,200 text messages collected from three academic WhatsApp groups over a three-month period. The analysis focuses on syntactic completeness, structural reduction, and dominant sentence patterns. The findings reveal that 58% of the analyzed sentences exhibit structural modifications, including subject ellipsis, predicate omission, fragmentation, and simplified single-clause constructions. Subject ellipsis emerges as the most frequent pattern, indicating a strong reliance on shared conversational context. Complex compound sentences appear less frequently, reflecting a tendency toward syntactic simplification and communicative efficiency. Reliability testing demonstrates high inter-coder agreement, confirming the consistency of classification results. These findings suggest that syntactic changes in digital communication are systematic adaptations to the characteristics of instant messaging environments rather than random deviations from formal grammar. The study provides preliminary evidence that digital syntax forms a distinct communicative pattern within semi-formal academic contexts. The results offer a foundation for further validation and extended investigation into the broader implications of digital communication practices on students’ formal writing competence.